Effectiveness of COSCIVOW (Contextualized Science Vocabulary Work-sheet) in The Level of Vocabulary Skills of Grade 10 Learner - Leonen, Christopher A. (Future Science / FSH-PH Publications, 2025)
As a subject rich in specialized vocabulary, science requires learners to develop strong reading and comprehension skills for a deeper con-ceptual understanding. Integrating literacy strategies, such as vocabu-lary instruction, can significantly benefit students (Venida, 2021). This study aimed to enhance the science vocabulary skills of Grade 10 learn-ers using the Contextualized Science Vocabulary Worksheet (COS-CIVOW). A quasi-experimental design compared an experimental group that received COSCIVOW-based instruction with a control group taught using traditional methods. Data analysis involved mean, percentage scores, and ANOVA.Results showed that learners' vocabulary skills were rated as Satis-factory before the intervention and improved to Very Satisfactory af-terward. A significant difference was observed between pre-and post-intervention vocabulary skills, indicating the effectiveness of COS-CIVOW. The findings suggest that COSCIVOW effectively encourages learners to engage with and understand science vocabulary, leading to improved language skills. Therefore, the researchers recommend in-corporating COSCIVOW in science instruction to enhance learners' vo-cabulary proficiency. They also advocate for its adoption in the Division of La Union to support broader educational improvement.